Industrialisation and the big push in a global economy - Udo Kreickemeier; Jens Wrona (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
In their famous paper on the "Big Push", Murphy, Shleifer, and Vishny (1989) show how the combination of increasing returns to scale at the firm level and pecuniary externalities can give rise to a poverty trap, thereby formalising an old idea due to Rosenstein-Rodan (1943). We develop in this paper an oligopoly model of the Big Push that is very close in spirit to the Murphy-Shleifer-Vishny (MSV) model, but in contrast to the MSV model it is easily extended to the case of an economy that is open to international trade. Having a workable open-economy framework allows us to address the question whether globalisation makes it easier or harder for a country to escape from a poverty trap. Our model gives a definite answer to this question: Globalisation makes it harder to escape from a poverty trap since the adoption of the modern technology at the firm level is impeded by tougher competition in the open economy.
urn:nbn:de:bsz:14-qucosa-224689
Keywords: F12; O14; F43; 330; Poverty Traps; Multiple Equilibria; International Trade; Technology Upgrading; General Oligopolistic Equilibrium